Loading pentapod deca(organo)[60]fullerenes with electron donors: From photophysics to photoelectrochemical bilayers - Matsuo, Yutaka; Ichiki, Takahiko; Radhakrishnan, Shankara Gayathri; Guldi, Dirk Michael; Nakamura, Eiichi (Journal of the American Chemical Society, 2010)
A pentapod deca(aryl)[60]fullerene, C (C H CO H) (C H Fc) Me (4; Fc = ferrocenyl), bearing five carboxylic acid and five ferrocenyl groups was synthesized through top and bottom functionalization of [60]fullerene by means of copper-mediated penta-addition reactions. For electrochemical measurements (i.e., E = 0.08 V, five-electron oxidation of the ferrocenyl groups; E = -1.89 and -2.28 V for the fullerene part vs Fc/Fc ), we used an ester-protected compound, C (C H CO Et) (C H Fc) Me (2), and 4 was probed by performing femtosecond flash photolysis experiments in a variety of organic solvents. Importantly, the formation of a radical ion pair state was corroborated with lifetimes of up to 333 ps in toluene. In complementary studies, penta(carboxylic acid)-penta(ferrocenyl) compound 4 was deposited on indium-tin oxide (ITO) electrodes with a surface coverage (i.e., 0.14 nmol/cm ) that corresponded to a unique bilayer structure. Decisive for the bilayer motif is the presence of five ferrocenyl groups, which are assembled with a merry-go-round-shaped arrangement on the [60]fullerene. The novel 4/ITO photoelectrode gave rise to a cathodic photocurrent with a 12% quantum yield in the presence of methyl viologen, whereas an anodic photocurrent was generated in the presence of ascorbic acid for a C (C H CO H) (C H ) Me (5)/ITO photoelectrode. Photophysical investigations revealed that the difference in photocurrent, that is, cathodic versus anodic photocurrents, is related to the nature of the excited state feature in 4 (i.e., charge separated state) and 5 (i.e., triplet excited state). The unique molecular architecture of 4, in combination with its remarkable donor-acceptor properties, validates the use of the pentapod deca(aryl)[60]fullerene in photoelectrochemically active molecular devices. © 2010 American Chemical Society.